Pengetahuan tentang Hipertensi dan Hubungannya dengan Kepatuhan Minum Obat di Kalangan Masyarakat Hipertensi - Ghofar Abdulloh, Ahmad Abdul; Yusuf, Ah.; Qur'aniati, Nuzul; Veriyallia, Vera (Jurnal Kesehatan Komunitas, 2024)
Non-adherence of hypertensive patients in the treatment of their disease has an impact on uncontrolled blood pressure which can worsen the patient's health status and even death. One important factor that must be considered in efforts to improve hypertension compliance is patient knowledge about the disease and the necessary management. This study aimed to determine the relationship between knowledge in supporting practice and compliance with hypertension sufferers in taking antihypertensive drugs. The research design used was cross-sectional descriptive analysis. The sample size for this study was 220 respondents who were recruited using purposive sampling techniques. Analysis of research data was carried out using the chi-square statistical test. A total of 51.8% of hypertensive patients had sufficient knowledge and 65.9% of hypertensive patients admitted that they were not compliant in taking the recommended medication. The value of the test results < α 0.05 (p= 0.000), which means that knowledge is significantly related to adherence to taking medication. Knowledge is the most important component that sufferers must have so that they can be actively involved in compliance practices. It is hoped that these findings can be used as material for consideration in formulating treatment interventions for people with hypertension about efforts to increase patient compliance in terms of taking anti-hypertensive medication.